The Transition Process of Youth Mobile Legends Jockey in Malang City as Part of the Risk Society - Pramana Herjati Putra Dionchi; Nanda Harda Pratama (Faculty of Social Science, Universitas Negeri Malang, 2022)
Currently games are not only used as entertainment, but also a source of income. Mobile Legends is a game used to be a source of income through jockey work. The perpetrators of Mobile Legends jockeys are carried out by young people in Malang City where in this phase the youth will be faced with choices related to maturity. This research is a qualitative research with the type of phenomenological research from Edmund Hussler. Determination of research subjects using the snowball sampling technique on young actors Mobile Legends jockeys in Malang City as research subjects. The number of informants in this study were 15 informants with details of 8 key informants and 7 supporting informants. The research was carried out for 11 months from December to October. This study uses Ulrich Beck's Risk Society Theory in analyzing the risks faced by young jockeys from the transition process carried out and solutions to deal with the risks. Where these youths carry out the transition process to become Mobile Legends jockeys by finding a solution to the risks they face, namely making jockey work a parttime job and slowly returning to people's lives in general.